PENGARUH HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN KARTU SELULER TELKOMSEL - Anissa Tadjuk Gayoni (Jurnal Utilitas, 2021)
This study aims to find the influence of prices on purchasing decisions. The research population of 80 people was entirely studied. The sampling technique used is the Incidental Sampling technique. After the data is declared normal and linear distribution based on normality test and linearity test, followed by variance analysis (ANAVA). Based on the results of linear regression calculation obtained Y = 51.10 + 0.477 x and the calculation result of ANAVA obtained Fhitung < Ftabel is 0.732 < 1.75. Hypothesis testing was conducted by calculating product-moment correlation and obtained Rhitung > Rtable 0.381 > 0.220 and Thitung > Ttabel 4.67 > 1.66 which means Ho was rejected and Ha accepted. Therefore, the results of this study concluded that there is an influence between Price and Purchasing Decision on Telkomsel Mobile Card Consumers.